Convection in Thin Shells of Icy Satellites: Effects of Latitudinal Surface Temperature Variations. Issue 8 (5th August 2019) - Weller, Matthew B.; Fuchs, Lukas; Becker, Thorsten W.; Soderlund, Krista M.
Abstract: We use three‐dimensional numerical experiments of thin shell convection to explore what effects an expected latitudinal variation in solar insolation may have on a convection. We find that a global flow pattern of upwelling equatorial regions and downwelling polar regions, linked to higher and lower surface temperatures ( T s ), respectively, is preferred. Due to the gradient in T s, boundary layer thicknesses vary from equatorial lows to polar highs, and polar oriented flow fields are established. A Hadley cell ‐type configuration with two hemispheric‐scale convective cells emerges with heat flow enhanced along the equator and suppressed poleward. The poleward transport pattern appears robust under a range of basal and mixed heating, isoviscous and temperature‐dependent viscosity, vigor of convection, and different degrees of T s variations. Our findings suggest that a latitudinal variation in T s is an important effect for convection within the thin ice shells of the outer satellites, becoming increasingly important as solar luminosity increases. Variable T s models predict lower heat flow and a more compressional regime near downwellings at higher latitudes, and higher heat flow and a more extensional regime near the equator. Within the ice shell, Hadley style flow could lead to large‐scale anisotropic ice properties that might be detectable with future seismic or electro‐magnetic observations. Plain Language Summary: Due to the curvature of planets, energy from the Sun varies from the equator to the poles. On airless bodies, such as the icy satellites, this difference in the Sun's energy leads to a variation in surface temperatures from an equatorial maximum to a polar minimum. This difference in surface temperatures for the icy satellites is a significant fraction of the temperature at the base of the ice shell or a significant fraction of the temperature differential that drives convection. We use numerical models of mantle convection in a three‐dimensional sphere to show that a poleward transport of material from equatorial regions emerges. Models with latitudinally variable surface temperatures predict lower heat flow, thicker conductive regions, and a more compressional stress state near downwellings at high latitudes, and higher heat flow, thinner conductive regions, and a more extensional stress state near the equator. A latitudinal variation in surface temperatures is likely an important effect for convection and the expression of surface deformation of the icy outer satellites and becomes increasingly important as the Sun ages. Key Points: A pole to equator variation in insolation can drive Hadley‐like convective cells in the ice shell, with polar downwelling and equatorial upwelling Velocity and surface deformation patterns can be diagnostic, with poleward compressive and equatorward extensional trends Latitudinal variation in surface temperature is likely an important effect for convection within the outer satellites